Use of transcriptomics and genomics to assess the effect of disinfectant exposure on the survival and resistance of Escherichia coli O157:H7, a human pathogen - Kirchner, Miranda; Nunez-Garcia, Javier; Duggett, Nicholas; Gosling, Rebecca J.; Anjum, Muna F. (Frontiers in Microbiology, 2024)
Disinfectants are essential for biosecurity, preventing the persistence and spread of zoonotic pathogens on farms and subsequent human infections. In this study, transcriptomics and genomics were utilised to assess the effect of disinfectant exposure on pathogenic Escherichia coli. The exposure of E. coli O157:H7 to sub-optimal concentrations of commonly used farm disinfectants elicited changes in both the transcriptome and genome. The transcriptomics identified upregulation of >300 genes and downregulation of >100 genes with functions, which included stress response, metabolism, transcription, transportation, membrane-associated and virulence genes. The phage shock protein (psp) operon was highly upregulated in response to a quaternary ammonium compound (QAC)-containing disinfectant, which has not previously been associated with a response to chemical stress. Disinfectant-adapted isolates generated by exposure to sub-lethal disinfectants levels demonstrated resistance to several common antibiotics and decreased sensitivity to biocides. Whole genome sequencing of the mutant strains indicated that they had acquired mutations in the genes associated with the upregulation of the multiple antibiotic resistance (MAR) efflux system (lon protease and marR) and topoisomerase genes (gyrA and gyrB). The disinfectant-adapted isolates also exhibited increased expression of transcription, respiration and several pH stress response genes localised in the “acid fitness island.” This study demonstrated that sub-optimal disinfectant concentrations allow E. coli O157:H7 to adapt and survive disinfection and develop antibiotic resistance. These changes could have implications for disease treatment and elimination on farms. Although E. coli O157:H7 and farm disinfectants were the focus of this study, we believe these findings are also applicable to other settings, including hospitals.